Coat Color of Korean Brindle Cattle and Melanocortin 1 Receptor (MC1R) mRNA: Variation of 3'-Untranslated Region and Expression - Hae-Lee Lee; Jae-Hee Park; Jong Gug Kim (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The objective of this study was to determine the breed differences in the 3'-untranslated region (UTR) of MC1R mRNA, which may be used to distinguish Korean brindle cattle (Chikso) from other breeds. We investigated the relationship between the variation of 3'-UTR of the MC1R mRNA and coat color among different breeds and the Korean brindle cattle with different coat colors. MC1R mRNA expression levels were determined in accordance with the coat color and hair colors of the tail. Total cellular RNA was extracted from the hair follicles of the tails in Hanwoo, Korean brindle cattle, Holstein and Hanwoo × Holstein crossbred cattle. After cDNA synthesis, PCR was performed. Sequences of the 3'-UTR of MC1R mRNA were analyzed. The 3'-UTR of the MC1R mRNA from different breeds of cattle did not show any variations. There were no variations in the 3'-UTR of the MC1R mRNA in Korean brindle cattle with different coat colors. The levels of MC1R mRNA expression in hair follicles of the tail varied substantially among the Korean brindle cattle with different coat colors, except yellow coat color. Correlation between the MC1R mRNA expression in the hair follicles of the tail and coat color may be present in the Korean brindle cattle, but not between the variations of 3'-UTR of MC1R mRNA and coat color. Further studies to determine the regulation of MC1R mRNA expression from the hair follicles of different coat colors will be beneficial in clarifying the role of MC1R in the coat colors of the Korean brindle cattle.